Advantages and Challenges of VR in Engineering Education - Ayu Amanah; Ihwan Ghazali; Handi; Yusrizal; Iwan Setiono (The Indonesian Institute of Science and Technology Research, 2026)
Virtual reality (VR) technology has the potential to revolutionise engineering education by providing students with immersive and interactive learning experiences not possible with conventional methods. Virtual reality can be used to simulate real-world environments and equipment, teach engineering concepts and principles, and prepare students for industry practices. However, the use of Virtual Reality in engineering education presents challenges, such as the limited availability and expense of VR equipment, the need for technical support and training for faculty and students, and the requirement for the creation and maintenance of Virtual Reality content. This issue was developed based on a narrative review and a literature review. The narrative review was conducted after the author studied and gathered the latest information. To effectively implement VR in engineering education, it is necessary to weigh the advantages and disadvantages of the technology and allocate resources accordingly. The benefit of VR in engineering education is increased accessibility to simulations and hands-on learning experiences, increased student engagement and motivation, the ability to visualize and manipulate 3D objects and concepts in a realistic environment, and the chance to safely test and experiment with equipment and processes. Future use of augmented reality (AR) and mixed reality (MR) technology in engineering education might provide students with even more immersive and interactive learning experiences. The use of Virtual Reality in engineering education has the potential to transform how engineering is taught and learnt by offering students more interesting and interactive learning experiences that better prepare them for success in the field.